2009
DOI: 10.1111/j.1525-1470.2009.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cutaneous Findings in Hospitalized Neonates: A Prospective Observational Study

Abstract: This study confirms that skin changes in the newborn are common, particularly desquamation, sebaceous hyperplasia, and transient toxic erythema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
47
4
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 9 publications
(16 reference statements)
20
47
4
9
Order By: Relevance
“…There were 21% neonates with Mongolian spots, mainly on buttocks in this study; reported incidence is 56% to 98% [13][14]. There were 15.59% with nappy rash in this study; Ferahbas A et al [14] reported incidence of 2% this difference may be due to financial reasons, our mothers do not change nappies as frequently as required leading to prolong stool contact resulting in nappy rash. Erythema toxicum neonatrum is the most common pustular dermatitis in newborns a benign condition requiring no intervention, presented in 15.50% of neonates in this study, reported incidence is 21-40% [15,16].…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…There were 21% neonates with Mongolian spots, mainly on buttocks in this study; reported incidence is 56% to 98% [13][14]. There were 15.59% with nappy rash in this study; Ferahbas A et al [14] reported incidence of 2% this difference may be due to financial reasons, our mothers do not change nappies as frequently as required leading to prolong stool contact resulting in nappy rash. Erythema toxicum neonatrum is the most common pustular dermatitis in newborns a benign condition requiring no intervention, presented in 15.50% of neonates in this study, reported incidence is 21-40% [15,16].…”
Section: Discussioncontrasting
confidence: 43%
“…Reported incidence is between 5% to 47.15% [10][11]. There were 21% neonates with Mongolian spots, mainly on buttocks in this study; reported incidence is 56% to 98% [13][14]. There were 15.59% with nappy rash in this study; Ferahbas A et al [14] reported incidence of 2% this difference may be due to financial reasons, our mothers do not change nappies as frequently as required leading to prolong stool contact resulting in nappy rash.…”
Section: Discussioncontrasting
confidence: 38%
“…This rate is close to those of CHAITHIRAYANON S. (16.9%) [13] and FERAHBAS A. (19.2%) [10]. The majority of the NNDs concerned the glabrous skin in our study as also noted KANE A.…”
Section: Discussionsupporting
confidence: 76%
“…The incidence of salmon patch in newborns is reported to be 44% in Caucasian neonates [2], 33.8% in Australian neonates [3], 26.2% in Iranian newborns, 13.8% in Indian newborns [4], 19.2% in Turkish newborn infants [5], and 59% in Spanish newborns [6]. Salmon patch usually disappears with aging, and the persistence of salmon patch shows a lower rate, though nuchal salmon patches in particular tend to persist [7,8].…”
Section: Commentarymentioning
confidence: 99%
“…In this studying, most nuchal salmon patches have a drop shape. [5], and 59% in Spanish newborns [6]. Salmon patch usually disappears with aging, and the persistence of salmon patch shows a lower rate, though nuchal salmon patches in particular tend to persist [7,8].…”
mentioning
confidence: 99%